Electrochemistry, electropolymerization and electrochromism of novel phthalocyanines bearing morpholine groups - Akyuz, Duygu; Demirbas, Umit; Koca, Atif; Celik, Fatih; Kantekin, Halit (Elsevier, 2020)
In this work, 4-(4-((4-morpholinophenylimino)methyl)phenoxy)phthalonitrile (3) and it's peripherally tetra substituted metal-free (4), zinc(II) (5), copper(II) (6) and nickel(II) (7) phthalocyanines were synthesized for the first time. The structural characterization of these novel compounds were performed with FT-IR, H-1 NMR, C-13 NMR, UV-Vis and mass spectroscopy. Electrochemical and spectroelec-trochemical characterizations of phthalocyanines (4-7) showed that while all phthalocyanines went to characteristics phthalocyanine ring and/or metal based reduction processes during the negative potential scans, all complexes were coated on the working electrode during the oxidation processes due to the cationic electropolymerizations of the 4-(4-((4-morpholinophenylimino)methyl)phenoxy) substituents. Changing the metal centers of phthalocyanine ring influenced the redox processes due to the different redox activities and effective nuclear charges of the metal centers. In addition to the electropolymerization ability of 4-(4-((4-morpholinophenylimino)methyl)phenoxy) substituent slightly affected the reversibility and peak positions of the redox processes. Indium tin oxide coated glass electrode (ITO) was coated with electropolymerized films of phthalocyanines to construct ITO/Poly-Phthalocyanine and these electrodes were tested as a potential electrochromic material. ITO/Poly-Phthalocyanine provided color change between green and blue with 1.2 s switching time, 18% optical contrast and 100% optical stability with 50 cronoamperometric (CA) cycles. These studies indicated possible usage of the electropolymerized films of phthalocyanines as possible building blocks for advanced electrochromic devices needing green-blue color change. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Morpholine; Metallo-phthalocyanines; Electrochemistry; Spectroelectrochemistry; (Oxidative) electropolymerization